A method for in vitro regional aerosol deposition measurement in a model of the human tracheobronchial tree by the positron emission tomography - Lizal, Frantisek; Belka, Miloslav; Adam, Jan; Jedelsky, Jan; Jicha, Miroslav (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2015)
Researchers have been studying aerosol transport in human lungs for some decades. The overall lung deposition can be predicted with sufficient precision nowadays. However, the prediction of local deposition remains an unsolved problem. Numerical modeling of aerosol transport can provide detailed data with such precision and spatial resolution which were unavailable in the past. Yet, the necessary validation of numerical results represents a difficult task, as the experimental data in a sufficient spatial resolution are hardly available. This article introduces a method based on positron emission tomography, which allows acquisition of detailed experimental data on local aerosol deposition in a realistic model of human lungs. The method utilizes the Condensation Monodisperse Aerosol Generator modified for a safe production of radioactive aerosol particles and a special measuring rig. The scanning of the model is performed on a positron emission tomography-computed tomography scanner. The evaluation of aerosol deposition is based on a volume radioactivity analysis in a specialized, yet publicly available software. The reliability of the method was tested and its first results are discussed in the article. The measurements performed using the presented method can serve for validation of numerical simulations, since the presented lung model digital geometry is available.
Keywords: Bronchi; trachea; Positron-Emission Tomography; Male; aerosoly; targeted drug delivery; mužské pohlaví; Aerosols; lékové transportní systémy; bronchy; Models, Biological; aerosol deposition; Humans; pozitronová emisní tomografie; positron emission tomography; biologické modely; Drug Delivery Systems; Trachea; lidé; Aerosol